Temporal trends, clinical patterns and outcomes of NAFLD‐related HCC in patients undergoing liver resection over a 20‐year period. Issue 9 (31st August 2017) - Pais, R.; Fartoux, L.; Goumard, C.; Scatton, O.; Wendum, D.; Rosmorduc, O.; Ratziu, V.
Summary: Background: Non‐alcoholic fatty liver disease (NAFLD) is an increasing cause of hepatocellular carcinoma (HCC) worldwide. NAFLD‐HCC often occurs in noncirrhotic liver raising important surveillance issues. Aim: To determine the temporal trends for prevalence, clinical characteristics and outcomes of NAFLD‐HCC in patients undergoing liver resection. Methods: Consecutive patients with histologically confirmed HCC who underwent liver resection over a 20‐year period (1995‐2014). NAFLD was diagnosed based on past or present exposure to obesity or diabetes without other causes of chronic liver disease. Results: A total of 323 HCC patients were included, 12% with NAFLD. From 1995‐1999 to 2010‐2014, the prevalence of NAFLD‐HCC increased from 2.6% to 19.5%, respectively, P = .003, and followed the temporal trends in the prevalence of metabolic risk factors (28% vs 52%, P = .017), while hepatitis C‐HCC decreased (from 43.6% to 19.5%, P = .003). NAFLD‐HCC occurred more frequently in the absence of bridging fibrosis/cirrhosis (63% of cases, P < .001 compared to other aetiologies). Within the NAFLD group, tumour characteristics were similar between F0‐F2 and F3‐F4 patients, except for a higher proportion of single nodules (95% vs 54%, P < .01). A total of 53% patients had tumour recurrence and 40% died. NAFLD‐HCC had similar time to recurrence and survival as HCCs of other aetiologies. Satellite nodules, tumour size, microvascular invasion and male sex but not the aetiology were independently associated with recurrence. Conclusion: Non‐alcoholic fatty liver disease increased substantially over the past 20 years among resectable HCCs. It is now the leading cause of HCC occuring without/or with only minimal fibrosis. NAFLD patients are older, with larger tumours while survival and recurrence rates are as severe as in other aetiologies. Abstract : Linked Content This article is linked to Balakrishnan and El‐Serag paper. To view this article visithttps://doi.org/10.1111/apt.14464 .